Doppler‐guided goal‐directed fluid therapy does not affect intestinal cell damage but increases global gastrointestinal perfusion in colorectal surgery: a randomized controlled trial. (1st December 2017) - Reisinger, K. W.; Willigers, H. M.; Jansen, J.; Buurman, W. A.; Von Meyenfeldt, M. F.; Beets, G. L.; Poeze, M.
Abstract: Aim: Individualized, goal‐directed fluid therapy (GDFT), based on Doppler measurements of stroke volume, has been proposed as a treatment strategy in terms of reducing complications, mortality and length of hospital stay in major bowel surgery. We studied the effect of Doppler‐guided GDFT on intestinal damage as compared with standard postoperative fluid replacement. Method: Patients undergoing elective colorectal resection for malignancy were randomized either to standard intra‐ and postoperative fluid therapy or to standard fluid therapy with additional Doppler‐guided GDFT. The primary outcome was intestinal epithelial cell damage measured by plasma levels of intestinal fatty acid‐binding protein (I‐FABP). Global gastrointestinal perfusion was measured by gastric tonometry, expressed as regional (gastric) minus arterial CO2 ‐gap (Pr‐ a CO2 ‐gap). Results: I‐FABP levels were not significantly different between the intervention group and the control group (respectively, 440.8 (251.6) pg/ml and 522.4 (759.9) pg/ml, P = 0.67). Mean areas under the curve (AUCs) of intra‐operative Pr‐ a CO2 ‐gaps were significantly lower in the intervention group than in the control group ( P = 0.01), indicating better global gastrointestinal perfusion in the intervention group. Moreover, the mean intra‐operative Pr‐ a CO2 ‐gap peak in the intervention group was 0.5 (1.0) kPa, which was significantly lower than the mean peak in the control group, of 1.4 (1.4) kPa ( P = 0.03). Conclusion: Doppler‐guided GDFT during and in the first hours after elective colorectal surgery for malignancy increases global gastrointestinal perfusion, as measured by Pr‐ a CO2 ‐gap.